2012
DOI: 10.1590/s1806-37132012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose grave com necessidade de internação em UTI

Abstract: Tuberculosis is a curable disease that can evolve to severe forms, requiring the treatment of the patients in an ICU, especially if there is a delay in the diagnosis or if it affects elderly patients, those on dialysis, or those with HIV infection or other states of immunosuppression, as well as in cases of multidrug resistant disease. Knowledge of the radiological presentation of the cases can help diagnose these severe forms, as can the introduction of new tests, such as the early detection of the etiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 31 publications
3
19
0
6
Order By: Relevance
“…Although HIV infection itself is a risk factor for mortality in the ICU, (28) our study concurred with others (4,13,29) in finding that HIV infection was not an independent risk factor for mortality among patients with TB in the ICU. Some authors have postulated that the short duration before death was insufficient time for HIV itself to cause mortality in patients with TB requiring ICU care, and that when TB was very severe, HIV infection was not likely to influence patient outcome any further.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although HIV infection itself is a risk factor for mortality in the ICU, (28) our study concurred with others (4,13,29) in finding that HIV infection was not an independent risk factor for mortality among patients with TB in the ICU. Some authors have postulated that the short duration before death was insufficient time for HIV itself to cause mortality in patients with TB requiring ICU care, and that when TB was very severe, HIV infection was not likely to influence patient outcome any further.…”
Section: Discussionsupporting
confidence: 89%
“…These were comparable to the mortality rates (range 47%-65.7%) reported from China, (9) Taiwan, (8) Korea (5) and Brazil. (13) Other centres have reported lower mortality rates in the range of 20%-30%. (3,4) A retrospective study by Erbes et al in Germany reported ICU mortality rates of 22.4% and in-hospital mortality of 25.9%, (4) which were significantly lower than the rates observed in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Os pacientes com tuberculose internados em UTIs podem desenvolver outras complicações, tais como pneumonia associada à VM, falência de múltiplos órgãos, choque séptico, insuficiência renal aguda, coagulação intravascular disseminada e sangramento digestivo. A insuficiência respiratória aguda causada por tuberculose e com necessidade de VM tem sido associada com taxas de mortalidade, entre 17,5% e 81,0% (69) .…”
Section: Causas De óBitounclassified